2017
DOI: 10.1088/2053-1591/aa6b22
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the properties of conventional and severe shot peened low alloy steel

Abstract: An investigation of the properties of conventional and severe shot peened low alloy steel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This results in improvement of fatigue strength of the base material. Severe shot peening enhances hardness and wear resistance [1]. Recent research works also proved that intensity of shot peening process increases the fatigue strength [2].…”
Section: Introductionmentioning
confidence: 97%
“…This results in improvement of fatigue strength of the base material. Severe shot peening enhances hardness and wear resistance [1]. Recent research works also proved that intensity of shot peening process increases the fatigue strength [2].…”
Section: Introductionmentioning
confidence: 97%
“…After AWJP, the surface topography of target material becomes rough, which decreases the fatigue life of the target material. 6,7 Taking Ti6Al4V as the object, Anwar et al studied the profile of a single dimple after AWJP under different incidence angles by simulation. 8 Sequentially, Sara Bagherifard et al established a finite element simulation model to assess the surface roughness of the target material, and the study found that the shot velocity, shot diameter, and coverage ratio all had a significant influence on the surface roughness.…”
Section: Introductionmentioning
confidence: 99%